DISTRIBUTION OF MINERAL RESOURCES AND AGGREGATES IN SAMBAS WATERS, WEST KALIMANTAN PROVINCE - Lugra, wayan (Buletin Sumber Daya Geologi, 2009)
Marine sediments of Sambas Waters, West Kalimantan, contain of five groups of minerals such as hydroxide oxides, silicates, sulfides, and carbonates. The dominant mineral in hydroxide oxides group is magnetite that composes about 0.00720% and lowest is 0.00310% of the sediments, followed by hematite, limonite, and rutile. Augite being the dominant mineral in silicate group was found in six samples with highest percentage of 0,.0091%, followed by casiterite and hornblende. Phyrite from the sulfide group, is present in six samples of seven sediment samples with average percentage of <1%. Dolomite is the only mineral that represents carbonate group and it was found in 7 samples with average percentage of less than 1%. While Mica minerals that occur in the study area are muscovite. Muscovite was observed in four sample of seven samples analysed, with highest percentage of 0.000771% and the lowest 0.00018%.Aggregates that have been exploited in the study area are andesite, dacite and sands that compose the alluvium and old volcanic units.